Arquitetura Art Déco nas escolas do Rio Grande do Sul no período do Estado Novo (1930-1950). - Cabral, Lisiê Kremer (2020)
This research presents a study about the standard schools in state of Rio Grande do Sul, idealized during the dictatorial peorid of president Vargas, with a temporal cut between 1930 and 1950. The work has three parts: (i) construction of theoretical references by bibliography, about education, school architecture in Brazil, Art Déco and political and ideological aspects of the time; (ii) identification of buildings and (iii) standard design analysis. During the Vargas administration in the 1930s, the educational system was reformulated to facilitate access to education, so a new school program was implemented to form a national unity through civic and moral concepts. In the same scenario were already being made imposing buildings with a progressive language, which had the intention of marking the political moment. The schools with a standard design, presented under an Art Déco architectural language, are located at this juncture and, besides their sumptuousness, they have elements that can be related to the nationalization of teaching, such as the banners and terraces used in civic moments. This study identified the circumstances that gave rise to these school buildings - the implementation of a new teaching method, along with the nationalization policy of immigrants and the new architectural language - and from this, we intend to legitimize the codes and symbols that these buildings have and their importance as instrument of government representation and social influence. To date, 39 similar educational institutions had been identified with variations that were influenced by the number of students - 200, 250, 350, 500 and 750. The analysis method used by the author was based on the collection and recombination of categories of essays based on the bibliography, allowing the elaboration of a synthesis that recovers the notion of style and relates the identified groups with the conceptual design instruments. The architectural analysis aims to point out and understand the standard design used, as well as its reference to modernity, and thus enhance the valorization of the school architecture Art Déco, seeking the historical preservation of these buildings.